Gambaran Perawatan Diri, Kepatuhan Pengobatan Dan Tingkat Kecacatan Pada Klien Kusta Di Kabupaten Banyumas - Wardani, Galuh Retno; Yulistiani, Mustiah (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: This study aims to find out the description of self-care, medication adherence, and the level of disability in leprosy clients in Banyumas Regency Method: This is qualitative research with a case study research design. Participants in this study were leprosy clients registered in the medical book of the Banyumas Health Office in 2019, aged from 26 to 79 years with a total of 6 people. Data collection was done through in-depth interviews. Results: This study has found 8 themes, namely hygiene, treatment of signs and symptoms, treatment management, leprosy description, routine activities, physical signs, and factors that aggravate leprosy. All of these themes affect how the leprosy clients perform their self-care daily, medication adherence they are undergoing, and to what extent the disability suffered by the clients. Conclusion: The leprosy client's self-care has been classified as good, only a few participants could not perform the five-moment handwashing aspects optimally. Treatment compliance of leprosy clients is at a medium level. There found 4 people in the category of disability level 1, and 2 people in the category of disability level 2